The Bodies in Charge of Animal Welfare: What They Do and What They Could Do? - Grignaschi, Giuliano; Redaelli, Veronica; Luzi, Fabio; Fornasier, Massenzio (Frontiers in Physiology, 2018)
The coming into force of the 2010/63/EU Standard, regarding the protection of animals used for scientific purposes, has made it mandatory for all establishments breeding, supplying and using said animals to have an Animal Welfare Body (AWB). The establishment of a body such as the AWB represents a strong innovation compared to previous regulations (Dir. 86/609/CEE). Building from the key concept of the 3 Rs, European Community legislators acknowledged that the effective safeguard of animal welfare depends in large part on the professional skills of personnel in charge of their care and use. The European Community legislators therefore identify a body inside the institution that houses the animals and entrust it with the task to stimulate and support the practical implementation of the 3 Rs, by informing on technical and scientific developments on the application of said principle and the subsequent training and follow-up training of personnel. The functions assigned by the Standard to the AWB therefore focus on technical-scientific support: to supply advice to personnel in charge of animals concerning their welfare, matters relating to their acquisition, housing, care and use, and to their integration/adoption (rehoming) at the end of their use. This approach is also emphasized by vesting the AWB with the responsibility to define and review internal monitoring and communication procedures pertaining to the welfare of the animals housed in the establishment, and to follow their development and the outcome of research projects concerning the effects produced on the animals used, supplying advice on activities that could result in possible improvements. Aware of the complexity and sensitivity of the role assigned to the AWB, and of the difficulty to put into practice the directions subject matter of the Standard, The European Commission, in the years following the issue of the Directive, appointed groups of experts with the task to formulate guidelines which would be beneficial both to the establishments and to control authorities of the various Member States and guarantee the implementation of effective and to control authorities of the various Member States and guarantee the implementation of effective and harmonized solutions.